Non-interactive modeling tools and support environment for procedural geometry generation - Morkel, Chantelle (Rhodes University, Faculty of Science, Department of Computer Science, 2006)
This research examines procedural modeling in the eld of computer graphics. Procedural modeling automates the generation of objects by representing models as procedures that provide a description of the process required to create the model. The problem we solve with this research is the creation of a procedural modeling environment that consists of a procedural modeling language and a set of non-interactive modeling tools. A goal of this research is to provide comparisons between 3D manual modeling and procedural modeling, which focus on the modeling strategies, tools and model representations used by each modeling paradigm. A procedural modeling language is presented that has the same facilities and features of existing procedural modeling languages. In addition, features such as caching and a pseudorandom number generator is included, demonstrating the advantages of a procedural modeling paradigm. The non-interactive tools created within the procedural modeling framework are selection, extrusion, subdivision, curve shaping and stitching. In order to demonstrate the usefulness of the procedural modeling framework, human and furniture models are created using this procedural modeling environment. Various techniques are presented to generate these objects, and may be used to create a variety of other models. A detailed discussion of each technique is provided. Six experiments are conducted to test the support of the procedural modeling benets provided by this non- interactive modeling environment. The experiments test, namely parameterisation, re-usability, base-shape independence, model complexity, the generation of reproducible random numbers and caching. We prove that a number of distinct models can be generated from a single procedure through the use parameterisation. Modeling procedures and sub-procedures are re-usable and can be applied to different models. Procedures can be base-shape independent. The level of complexity of a model can be increased by repeatedly applying geometry to the model. The pseudo-random number generator is capable of generating reproducible random numbers. The caching facility reduces the time required to generate a model that uses repetitive geometry.
Keywords: Computer graphics -- Mathematical models; Three-dimensional display systems; Computer simulation